2015
DOI: 10.1021/acs.macromol.5b00818
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation in Isotactic Polypropylene at Large Strains during Tensile Deformation at Elevated Temperatures

Abstract: Two quenched isotactic polypropylene samples with different molecular weight were used to explore the sudden stress whitening activated at large strains during stretching at elevated temperatures via the ultrasmall-angle Xray scattering technique. This kind of whitening was confirmed to be caused by the creation of cavities within the highly oriented samples. The critical strain for initiating the stress whitening increases with the increase of stretching temperature and molecular weight whereas the critical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
133
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(140 citation statements)
references
References 35 publications
6
133
1
Order By: Relevance
“…The initiation of cavitation was found to be around the yield point, which was coincident with the observation of previous works . However, Lu et al recently found that the cavitation was triggered in the quenched isotactic polypropylenes stretched to a highly oriented state (far away beyond yield point) at elevated temperatures. They attributed this cavitation to the failure of the highly oriented amorphous network connecting adjacent fibrils.…”
Section: Introductionsupporting
confidence: 88%
“…The initiation of cavitation was found to be around the yield point, which was coincident with the observation of previous works . However, Lu et al recently found that the cavitation was triggered in the quenched isotactic polypropylenes stretched to a highly oriented state (far away beyond yield point) at elevated temperatures. They attributed this cavitation to the failure of the highly oriented amorphous network connecting adjacent fibrils.…”
Section: Introductionsupporting
confidence: 88%
“…Considering the fact that generation of highly oriented Form I crystallites can hinder the phase transition of residual Form II crystallites, this impediment effect may be based on the localization of macroscopic stretching on interstack tie chains. Men and coworkers have revealed that interstack tie chains induced by crystallites stretching can bear the majority of stretching strength . Therefore, the macroscopic deformation applied is compensated by the interstack slippage.…”
Section: Resultsmentioning
confidence: 99%
“…After transformation, the mechanical property of crystallite sample is improved . As the concentration of transformed Form I increases to certain content, they can be cooperatively connected to build up the gel‐like network through the interstack chains . These lamellae with improved mechanical property act as the physical crosslinks and hold the major stretching externally imposed.…”
Section: Resultsmentioning
confidence: 99%
“…To further express the dimension of the scattering object, the Ruland method was chosen to calculate the bridge crystal length, which was described as follows: Bobs=2π〈〉Lshishq+Bϕ where B obs , L shish , and B ϕ denoted the integral breadth, the length, and the misorientation of bridge crystal structure, respectively. The detailed calculating method was described by Men et al…”
Section: Methodsmentioning
confidence: 99%